Prognostic Significance of Sarcopenia in Advanced Biliary Tract Cancer Patients - Lee, Byung min; Cho, Yeona; Kim, Jun Won; Jeung, Hei Cheul; Lee, Ik Jae (Frontiers in Oncology, 2020)
Background: Sarcopenia, systemic inflammation, and low muscularity significantly impact the survival of cancer patients. However, few studies have investigated how sarcopenia and systemic inflammation affect the prognosis of biliary tract cancer with distant metastasis. In this study, we investigated the association between sarcopenia with systemic inflammation and prognosis of metastatic biliary tract cancer. Materials and Methods: Data collected from 353 metastatic biliary tract cancer patients from 2007 to 2016 were analyzed. To evaluate the skeletal muscle mass, computed tomography images at the upper level of the third lumbar vertebra (L3) were used. Sarcopenia was defined using the Japan Society of Hepatology guideline; L3 muscle index <42 cm2/m2 for male and <38 cm2/m2 for female patients. Systemic inflammation was evaluated using the neutrophil lymphocyte ratio (NLR). Patients with NLR > 3 were categorized into the inflammatory category. The overall survival (OS) and progression free survival (PFS) were analyzed. Subgroup analysis was performed on those who received gemcitabine/cisplatin (GP) chemotherapy and depending on the presence of sarcopenia and inflammation. Results: Patients with sarcopenia showed lesser 1-year OS than those without (25.5 vs. 38.2%, p = 0.019). The patients with high NLR (NLR > 3) were associated with a shorter OS than were those with a low NLR (NLR ≤ 3) (21.0 vs. 52.8%, p < 0.001). Based on these results, we categorized the patients into three groups; sarcopenia accompanied by high NLR, no sarcopenia and low NLR, and either sarcopenia or high NLR. The OS of patients was well-stratified according to this grouping (1-year OS; 18.3 vs. 30.3 vs. 55.8%, p < 0.001). Concordant with OS results, the PFS was well-stratified based on the presence of either sarcopenia or high NLR (Sarcopenia; 9.5 vs. 19.4%, p < 0.001, NLR; 10.0 vs. 23.4%, p < 0.001). The PFS was significantly associated with high NLR and sarcopenia (1-year PFS; 7.8 vs. 13.0 vs. 27.9%, p < 0.001). Conclusion: Sarcopenia with inflammation was associated with inferior OS and PFS. In addition, sarcopenia accompanied by inflammation was associated with poor prognosis. Conservative treatments such as nutritional support, exercise, and pharmacologic intervention could help metastatic biliary tract cancer patients to overcome sarcopenia and the inflammatory status.